Spatial biases in processing mirror letters by literate subjects - Patro, Katarzyna; Gross, Antonia; Friedrich, Claudia (Reading & writing, 2025)
Preschool children often confuse letters with their mirror images when they try to read and write. Mirror confusion seems to occur more often in line with the direction of script (e.g., left-to-right for the Latin alphabetic script), suggesting that the processing of letter orientation and text directionality may be interrelated in preliterate age. When children go to school, mirror mistakes in writing/reading letters disappear. Here we ask whether the processing of letter shapes and text direction are still related in readers at different proficiency levels. Literate subjects – school children from the 1st and 4th grades and adults – decided under time pressure whether a displayed letter was oriented correctly or incorrectly (mirrored). We observed that reaction times were faster when a letter was oriented rightward, i.e. in line with the cultural text direction (left-to-right), but we did not find any differences between the groups. We conclude that, even if mirror mistakes disappear during primary school years, letter shapes are still processed in a close relation to the left-to-right reading direction in the Latin script.